(untitled) (Bangladesh Journal of Medical Science, 2021)
Objective: Physical activity (PA) is one of the most important determinants for physical fitness (PF) in adolescence and young age. The previous study showed that most medical students as part of young population were found to be physically inactive. Our study aims to evaluate the correlation between PA and PF status among medical students. Materials and methods: One hundred and twenty five medical students of UNISSULA were enrolled in this study. PA level was measured using international physical activity questionnaire (IPAQ)-short form. PF status was evaluated by cardiorespiratory capacity (VO2max score), handgrip muscle strength (HGS), and body composition (fat persentage and BMI). The data were analyzed using pearson correlation analysis. Results and discussion: The majority of PA level among participants were low. There was a correlation between PA level and sex (p= 0.001, r = 0.272), PA level and BMI (p = 0.001, r = 0.264), PA level and HGS score (p=0.000, r = 0.345). However, there was no correlation between PA level and VO2max or fat percentage. Conclusion: The PA level and PF status among participants were considered to be low and fair, respectively. Only one component of PF status (HGS) was correlated with PA level. Further investigations on the correlation between PA level and PF status using more objective methods are needed especially when involving medical students. Bangladesh Journal of Medical Science Vol.20(3) 2021 p.625-630